Corporate Social Responsibility: Theory, Practice and Its Impact on The Company - Arumega Zarefar; Tjiptohadi Sawarjuwono (Politeknik Caltex Riau, 2021)
This paper aims to provide a comprehensive discourse on Corporate Social Responsibility from the theory, components, and impacts on a company and its stakeholders. The research method is conceptual paper. The paper is developed through identifying issues about CSR from existing literature, discussing related theories, analyzing the relationships between GCG and CSR, and explaining stakeholder interactions in CSR practices. The findings of this research indicated that not only do CSR practices have a positive impact on the environment and society, but also affect the survival and sustainable development of the company. In addition, CSR practices are closely related to the implementation of GCG and interactions between stakeholders. Analysis of the theory and literature in this study is carried out comprehensively so that it provides a complete picture of CSR practices. Keywords: Corporate social responsibility, Good Corporate Governance, stakeholder interaction